If Pets Are Family: Pet Loss and the Need for Grief Equity in One Health - Michele L Whitney (Journal of One Health Systems, 2026)
One Health frameworks increasingly recognize pets as integral to human health and well-being. However, these models often overlook the health and equity implications of pet loss. Culturally mediated grief experiences following pet bereavement represent a critical grief equity gap in One Health systems. Drawing on findings from a qualitative study of African American adults who experienced pet loss, along with existing literature, this Viewpoint highlights how pet loss is not only an emotional experience but also a socially structured one shaped by cultural norms, social recognition, and access to support. These dynamics contribute to inequities in how grief is experienced and addressed across communities. Integrating grief equity into pet-inclusive models of care can strengthen interdisciplinary responses to pet bereavement and support more inclusive, equitable approaches to health across the lifespan.
Keywords: human-animal bond; One Health; pet loss; pet bereavement; grief equity; Veterinary Social Work